THE USE OF GLUCOSAMINE AND THE INCREASE OF IOP: A LITERATURE REVIEW - Wega Yusan Wira Perdana; Pirlina Umiastuti; Nabila Putri Wardhani; Amirah Jasmine; Nur Milati Bani Mostavan; Nadhilah Putri Ghaisani; Audi Salman Faza (Universitas Airlangga, Surabaya, Indonesia, 2022)
Highlights: 1. There are differences in the result of the use of glucosamine and the increase of intraocular pressure.2. There are many other factors that may contribute to the increase in the intraocular pressure other than the use of glucosamine such as races, genetics, different dose, and duration of glucosamine use. Abstract: Background: Glucosamine is an amino monosaccharide that can directly stimulate the synthesis of glycosaminoglycans in the cartilage. It has been widely used as an osteoarthritis treatment. However, several literatures show the possible side effects of glucosamine, such as increased intraocular pressure (IOP). Objective: The objective of this study was to determine if there was any correlation between the use of glucosamine and the increase in IOP. Material and Method: This was a descriptive qualitative study that implied a systematic review design. The study sample consisted of patients with osteoarthritis (OA) and glaucoma in Iran, Indonesia, Thailand, the USA, and India between 2013 and 2018. The literature search was conducted on a database (PubMed and Google Scholar) and selected using inclusion and exclusion criteria. Discussion: The research identified 5 studies on the use of glucosamine and the increase of IOP. Two articles provide significant results on the correlation between the use of glucosamine and the increase of IOP (P < 0.05). In addition, two studies showed significant IOP reduction outcomes after discontinuation of glucosamine (P < 0.05). A case series indicated an increase in IOP during the 6th month of glucosamine use but still at normal value. Conclusion: Many other factors contribute to IOP growth, other than the use of glucosamine. Therefore, a large-scale randomized clinical trial or a multicentre cohort study using the same parameters is still needed to improve the quality of the subsequent systematic review